ARRANGEMENT OF LAW BY STATE FINANCIAL AUTHORITY IN REALIZING NATIONAL BANKING INDUSTRY THAT’S HEALTHY AND DYNAMIC. - Muammar Arafat Yusmad (Faculty of Law, Universitas Jenderal Soedirman, 2015)
The development of national banking nowadays are growing fast, competitive and integrative. One problem of Indonesian banking system related with practicing law arrangement which is a harmonization process toward legislations. The focus problems are: law arrangement in banking governance, the procedure of the law arrangement in achieving national bank industry which are healthy and dynamic. As intermediary institutions, bank should be in a healthy condition in order to gain public confidence and deserve to increase national economic growth. Based on the conceptual discussion, obtained arguments are: (1) The law arrangement of national banking should be done coodinately between Otoritas Jasa Keuangan (OJK) and Bank Indonesia (BI); (2) Procedure of law arrangement according to the function and authority of OJK and BI which the urgent subjects are to avoid conflict of norm, overlapping policies and limited validity of norm of the law case which happen and will be happen; (3) banking law arrangement include bank arrangement and supervision system, strengthening internal condition of the bank, empowering and protecting consumer with complaints mechanism and follow-up which are clear and measurable. Key Words: Law arrangement, banking, health and dynamic bank.